Direct evidence for continuous radar reflector originating from changes in crystal-orientation fabric - Eisen, O.; Hamann, I.; Kipfstuhl, S.; Steinhage, D.; Wilhelms, F. (HAL CCSD, 2007)
International audience The origin of a strong continuous radar reflector observed with airborne radio-echo sounding (RES) at the EPICA deep-drilling site in Dronning Maud Land, Antarctica, is identified as a transition in crystal fabric orientation from a vertical girdle to an increased single-pole orientation seen along the ice core. The reflector is observed with a 60 ns and 600 ns long pulse at a frequency of 150 MHz, spans one pulse length, is continuous over 5 km, and occurs at a depth of about 2025?2045 m at the drill site. Changes in conductivity as reflector origin are excluded by investigating the ice-core profile, synthetic RES data, and a RES profile with different electromagnetic polarisation azimuths. The reflector's magnitude shows maximum values for polarisation parallel to the nearby ice divide and disappears for polarisation perpendicular to it, identifying the orientation of the girdle to lie in the vertical plane parallel to the ice divide. Observations allow us to extrapolate the crystal orientation feature along the reflector in space, with implications for ice-sheet dynamics and modeling.